The Russian Transition through his Elites. A Historiographical Approach - Miguel Alonso Ibarra (El Futuro del Pasado, 2013)
The main objective of this article is to analyze the different perspectives that have been developed around the Russian transition. In this sense, we will try to tackle, from a global perspective, the debate around who were the driving forces of the process of political change. Thus, we will pay attention to both the approaches maintaining that these driving forces were the elites, that is to say, that the process was driven «from above», and those who focus on social movements exogenous to the system, arguing that the process was driven «from below». At the same time, we will analyze the perspectives dealing with the strategies adopted by the elites in their effort to maintain their influences in the construction of the new democratic states. Finally, we will study how these strategies influenced both the process itself and the configuration of the new political scenario in Russia and Eastern Europe.